Control research and application of conventional operations without real-time networks - Zhengfeng ZHANG (Dianxin kexue)
On the basis of researching the timing agreement mechanism and mirror synchronization operation to ob-tain keys under the condition of no network,a logic control method was proposed based on cryptography control,non-real-time virtual communication and computing keys according to agreement,which could be well applied to dynamic authentication and switch operation of intelligent locks or switches without real-time communication net-work coverage.By using the intelligent terminal with the ability of agreed operation,a kind of “control network of cryptography” without real-time communication network was established,which could be used as a useful supple-ment to the IoT technology without communication coverage,as well as a remote object in a fixed location to transfer the right of management or use according to the order of calculation.By using the computing power of the terminal instead of the communication power of the remote end,without the need to build a backstage communication network and the communication expenses during the waiting period.